Pengaruh Cafe Atmosphere, Customer Experience, Dan Harga Terhadap Minat Beli Ulang Pada Cafe Wai Teman Minum Kamu Kabupaten Toraja Utara - Yodi Salo Tangkuan; Althon K. Pongtuluran; Chrismesi Pagiu (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study is to find out whether there is an influence of cafe atmosphere, customer experience and price on repurchasing intentions at Cafe Wai Your Drinking Friends. Data collection methods are: Questionnaire and Documentation. Data were analyzed quantitatively with Multiple Liner Regression. The results of calculations with the F test analysis obtained an F count of 53.851 with an F table of 3.094. Based on the results of calculations with the T test on the cafe atmosphere variable, the result is T count (9.688) > T table (1.98498). and on the customer experience variable T count (-2.906) < T table (1.98498), then on the price variable T count (0.831) < T table (1.98498 The conclusion is that the cafe atmosphere variable has an effect on repurchasing interest at cafe Wai Your Drinking Friends and the customer experience variable and price have no effect on repurchasing interest at cafe Wai your drinking buddy, North Toraja Regency.